2017
DOI: 10.3832/ifor2251-010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil-applied lead on mineral contents and biomass in Acer cappadocicum, Fraxinus excelsior and Platycladus orientalis seedlings

Abstract: Phytoremediation is an effective and affordable approach to extract or remove lead from contaminated soil. An understanding of the physiological responses of different species subjected to heavy metal contamination is necessary before considering their use for environmental clean-up. The objective of this study was to assess the effect of lead (Pb) on growth and nutrient uptake in three forest species native to Iran: Cappadocian maple (Acer cappadocicum), European ash (Fraxinus excelsior) and Oriental aborvita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…showed that CI values of Cd increased in the seedlings with an increase in the concentration of Cd and Pb in the soil, while the effect of the interaction between Cd and Pb showed that the highest CI value was 490.812 when the interaction (110 Cd and 550 Pb) mg kg -1 and this value was superior significantly on all the interference values, and the CI of 184.298 at the interaction (110 Cd and zero Pb) mg kg -1 significantly exceeded on the control, and the results of this study surpassed the results of Chandra and Hoduck (11), in their study of the effect of a mixture of Cu, Cd, Cr and Zn at concentrations of 0, 5, 50, 100, 200 and 500 mg L -1 on four different poplar hybrids, the results showed that the highest CI value for Cd was 35.69 when interfering 500 mg L -1 for Cd, Zn, Cu and Cr in the TD225 hybrid, which significantly outperformed all other the hybrids values. Effect of Cd and Pb on TF of Pb: From the results of Duncan's multiple range test (Table 15), it appears that the highest value of TF for Pb was 5.702 at the control which was significantly superior to all other TF values, and the value was 1.675 at the interaction (110 Cd and 550 Pb) mg kg -1 , which was significantly higher on the TF value of 0.431 at the interaction (550 Pb and zero Cd) mg kg -1 , also the control value significantly outperformed the TF value of 0.431 at the interaction (550 Pb and zero Cd) mg kg -1 and the TF value of 1.879 at the interaction (110 Cd and zero Pb) mg kg -1 , the values of this study were close to the results of researchers Abbasi et al (1) (25), that value of BCF (>1) in the plant is a good indication of phytoremediation of soils contaminated with the heavy metals (35,39).…”
Section: Effect Of CD and Pb On Ci Of Cdsupporting
confidence: 90%
See 1 more Smart Citation
“…showed that CI values of Cd increased in the seedlings with an increase in the concentration of Cd and Pb in the soil, while the effect of the interaction between Cd and Pb showed that the highest CI value was 490.812 when the interaction (110 Cd and 550 Pb) mg kg -1 and this value was superior significantly on all the interference values, and the CI of 184.298 at the interaction (110 Cd and zero Pb) mg kg -1 significantly exceeded on the control, and the results of this study surpassed the results of Chandra and Hoduck (11), in their study of the effect of a mixture of Cu, Cd, Cr and Zn at concentrations of 0, 5, 50, 100, 200 and 500 mg L -1 on four different poplar hybrids, the results showed that the highest CI value for Cd was 35.69 when interfering 500 mg L -1 for Cd, Zn, Cu and Cr in the TD225 hybrid, which significantly outperformed all other the hybrids values. Effect of Cd and Pb on TF of Pb: From the results of Duncan's multiple range test (Table 15), it appears that the highest value of TF for Pb was 5.702 at the control which was significantly superior to all other TF values, and the value was 1.675 at the interaction (110 Cd and 550 Pb) mg kg -1 , which was significantly higher on the TF value of 0.431 at the interaction (550 Pb and zero Cd) mg kg -1 , also the control value significantly outperformed the TF value of 0.431 at the interaction (550 Pb and zero Cd) mg kg -1 and the TF value of 1.879 at the interaction (110 Cd and zero Pb) mg kg -1 , the values of this study were close to the results of researchers Abbasi et al (1) (25), that value of BCF (>1) in the plant is a good indication of phytoremediation of soils contaminated with the heavy metals (35,39).…”
Section: Effect Of CD and Pb On Ci Of Cdsupporting
confidence: 90%
“…From the results of Duncan's multiple range test (Table17) it appears that BCF value for Pb reached 2.560 at the interaction between (110 Cd and 550 Pb) mg kg-1 , and significantly decreased from the value 3.026 at the interaction of (550 Pb and zero Cd) mg kg -1 , and it was significantly higher than the BCF of 3.026, the values of this study were close to Abbasi et al(1) in their study on seedlings of Acer cappadocicum, Fraxinus excelsior and Platycladus orientalis, as it showed the significant superiority over all values of BCF for Pb at the control their values approached 3, 2, and 1.6 in P. orientalis, F. excelsior and A. cappadocicum seedlings, respectively. The BCF value in the plant depends on the type and concentration of heavy metals in the soil as well as on the plant type and the surrounding environmental conditions…”
supporting
confidence: 88%
“…Increasing Pb application in the soil (from 100 to 500 mg kg -1 ) did not affect the dry weight of roots of all species, while a gradual decrease was detected in leaves and shoots, with the highest inhibition in P. orientalis. This species, however, showed the highest translocation factor values, tolerance index and bioconcentration factor, indicating a possible use of this conifer species for remediation of Pb-polluted soils (Abbasi et al 2017). The bioconcentration factor (BF) is defined as the ratio of metal(loid) concentration in aerial biomass to that in soil, and the translocation factor (TF) the ratio of metal(loid) concentration in shoots to that in roots, both factors taking values >1 in accumulators and <1 in excluders; the tolerance index (TI) is the percent of the organ's growth of the treated plant compared to the growth of the control plant (McGrath & Zhao 2003, Turner et al 1991.…”
Section: Woody Speciesmentioning
confidence: 90%
“…The increased input of toxic heavy metals can potentially threaten ecosystems and human health, and has become an issue of great concern (Fajardo et al 2019). Since forest ecosystems filter out the airborne pollutants, heavy metal loading from the atmosphere is especially high in the soils under forests (Abbasi et al 2017, Utermann et al 2019, resulting in a significant change of the heavy metal concentrations on both regional and international scales (Utermann et al 2019). Although pollutant emissions from factories have recently been considerably reduced, the increased heavy metals will persist for many decades and move rather slowly through the soil.…”
Section: Introductionmentioning
confidence: 99%